Factors influencing germination of six wetland Cyperaceae - (:unkn) unknown (My University, 1997)
In order to determine factors which may affect the differential seed germination of six members of the Cyperaceae which occur together in newly revegetated sedge meadow, seeds were tested for germ inability at three storage conditions. Seeds were also germinated at two alternating temperature regimes, 21/25° and 25/32°C. Germination of dry stored Carex hystericina and C. vulpinoidea was greater at the higher alternating temperature of 25/32°C while Scirpus atrovirens and S. cyperinus dry stored seed had a similar germination response at both alternating temperatures. Most of the moist-cool stored (stratified) seeds of the six species germinated well regardless of temperature. Seeds of these tussock-forming sedge meadow species germinate best when stratified, and higher temperatures may assist in breaking dormancy of dry stored seed. Dry-cool storage slows after ripening and seed may re-enter dormancy.
Keywords: seed germination; Cyperaceae; sedge meadow; Carex; Scirpus